Imagined communities : reflections on the origin and spread of nationalism - Anderson, Benedict R. O'G. (Benedict Richard O'Gorman), 1936 (London ; New York : Verso, 2006)
'Imagined Communities' examines the creation and function of the 'imagined communities' of nationality and the way these communities were in part created by the growth of the nation-state, the interaction between capitalism and printing and the birth of vernacular languages in early modern Europe
-- Introduction -- Cultural roots -- The origins of national consciousness -- Creole pioneers -- Old languages, new models --- Official nationalism and imperialism -- The last wave -- Patriotism and racism -- The angel of history -- Census, map, museum -- Memory and forgetting -- Travel and traffic: on the geo-biography of Imagined communities
Includes bibliographical references (pages 230-233) and index
Keywords: Nationalism -- History